HUBUNGAN PENGETAHUAN TENTANG PEMAKAIAN GIGI TIRUAN DENGAN TINGKAT KEPERCAYAAN DIRI LANSIA DI POSYANDU LANSIA RANGGEN SURABAYA - Sasi, Ajeng Diva Nawang; Larasati, Ratih; Mahirawatie, Ida Chairanna (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2025)
ABSTRACT Background: The problem in this study is the lack of knowledge regarding denture use in the elderly and their level of self-confidence. This study aims to determine the relationship between knowledge about denture use and self-confidence in the elderly at the Ranggen Elderly Health Post (Posyandu Lansia) in Surabaya. Methods: This research was an analytical cross-sectional study with a sample of 35 elderly people at the Ranggen Elderly Health Post (Posyandu Lansia) in Surabaya. The data collection instrument was a questionnaire. The analysis technique used the chi-square test. Results: The test results from the research obtained a ρ value of 0.00 or a significance ρ score below (0.05). Conclusion: The conclusion of this study is that there is a relationship between the knowledge of the elderly about using dentures and the level of self-confidence of the elderly at Posyandu Ranggen Surabaya.. Keywords: Knowledge, Dentures, Self-confidence, Elderly.